Effects of Acetaminophen, NSAIDs, Gabapentinoids, and Their Combinations on Postoperative Pulmonary Complications After Total Hip or Knee Arthroplasty. Issue 10 (26th February 2020) - Ohnuma, Tetsu; Raghunathan, Karthik; Ellis, Alan R; Whittle, John; Pyati, Srinivas; Bryan, William E; Pepin, Marc J; Bartz, Raquel R; Krishnamoorthy, Vijay
Abstract: Objective: Multimodal analgesia has gained popularity in total hip arthroplasty (THA) and total knee arthroplasty (TKA), but large multicenter studies evaluating specific analgesic combinations are lacking. Design: A retrospective study using the Premier Healthcare Database (2009–2014). Subjects: Adults who underwent elective primary THA or TKA. Methods: We categorized day-of-surgery analgesic exposure using eight mutually exclusive categories: acetaminophen (Ac), nonsteroidal anti-inflammatory drugs (Ns), gabapentinoids (Ga; gabapentin or pregabalin), Ac+Ns, Ac+Ga, Ns+Ga, Ac+Ns+Ga, and none of the three drugs. Multilevel models measured associations of the analgesic categories with a composite of postoperative pulmonary complications (PPCs). Results: Among 863, 139 patients, 75.2% received at least one of the three drugs. In multilevel models, compared with none of the three drugs, Ga use was associated with increased odds of PPCs when used alone (adjusted odds ratio [aOR] = 1.35, 95% confidence interval [CI] = 1.27 to 1.44), combined with Ac (aOR = 1.16, 95% CI = 1.08 to 1.26), or combined with Ns (aOR = 1.28, 95% CI = 1.21 to 1.34). In contrast, the Ac+Ns pair was associated with decreased odds of PPCs (OR = 0.86, 95% CI = 0.83 to 0.90) and lower opioid consumption. Ac+Ns+Ga was not associated with PPCs, whereas it was associated with the lowest opioid consumption on the day of surgery. Conclusions: Gabapentinoids, alone and in single combination with either acetaminophen or nonsteroidal anti-inflammatory drugs, were associated with higher PPCs, whereas the Ac+Ns pair was associated with fewer PPCs and an opioid-sparing effect. Ac+Ns+Ga was not associated with PPCs, whereas it was associated with the lowest opioid consumption on the day of surgery.